The role of domestic mechanisms in post conflict reconstruction and development in Africa: the case of Rwanda - Munyangabo, Joseph (My University, 2010)
Abstract Post conflict reconstruction in Africa and the role of international community in post conflict recovery have dominated global debates especially in the post cold war era. The arguments range from whether international policies and external intervention in post war countries helps in their economic recovery and ensures that there is no resurgence into war or whether it in fact plays a role in keeping the post war countries incapacitated, poverty stricken, dependent and susceptible to future conflicts. This research was motivated by the need to demonstrate how home grown mechanisms have higher chances of attaining sustainable peace and development as compared to the models imported from Western countries. Post 1994 Rwanda presents an ideal case study due to its unique approach to post-conflict reconstruction. This research report investigated the different domestic programs adopted by the Rwandan government in its reconstruction process; the electoral reforms; infrastructure reforms; the refinement of the economic development and poverty reduction strategy program to suit the Rwandan situation which was the focus of the transitional government. This report further analysed the national reconstruction programs namely; the national unity and reconciliation commission and the Gacaca system of justice. It was observed that these domestic programs registered significant successes in promoting peace and stability and propelled the nation to a quick and sustainable recovery. It is concluded however, that even though Rwanda has been moving in the right direction in its reconstruction process, there are still considerable challenges that may threaten the national achievements made so far.